The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1007/s11664-009-0979-9
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Single-Phase β-Zn4Sb3 Prepared by a Mechanical Grinding Method

Abstract: Single-phase b-Zn 4 Sb 3 materials were prepared by mechanical grinding (MG). Source materials for the Zn 4 Sb 3 ingots were prepared using three different processes after the direct melting of constituent elements. In process 1, the ingot was obtained by quenching the melt in water within an evacuated quartz ampoule. In process 2, the ingot was heat-treated for 100 h at 723 K after process 1. In process 3, the ingot was heat-treated for a total of 200 h in two stages at 723 K and 673 K after process 1. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…5) In a moderate temperature range (450-650 K), -Zn 3:83þ Sb 3 has a lot of advantages because the ZT of -Zn 3:83þ Sb 3 is the highest in this temperature range. [6][7][8][9][10][11][12][13][14] However there are difficulties when attempting to control the stoichiometry for the manufacture of Zn 3:83þ Sb 3 specimens. 15) Toberer and Snyder et al reported a stable phase stoichiometry expressed as Zn 3:83 Sb 3 at room temperature as opposed to the conventional stoichiometric composition Zn 4 Sb 3 or the charge-balanced composition Zn 3:9 Sb 3 .…”
Section: Introductionmentioning
confidence: 99%
“…5) In a moderate temperature range (450-650 K), -Zn 3:83þ Sb 3 has a lot of advantages because the ZT of -Zn 3:83þ Sb 3 is the highest in this temperature range. [6][7][8][9][10][11][12][13][14] However there are difficulties when attempting to control the stoichiometry for the manufacture of Zn 3:83þ Sb 3 specimens. 15) Toberer and Snyder et al reported a stable phase stoichiometry expressed as Zn 3:83 Sb 3 at room temperature as opposed to the conventional stoichiometric composition Zn 4 Sb 3 or the charge-balanced composition Zn 3:9 Sb 3 .…”
Section: Introductionmentioning
confidence: 99%